Implementasi Desentralisasi Dalam Pengelolaan Perikanan - Muhayat; Rina Haslita (Bahasa Indonesia, 2021)
Since the early 1990s, various discourses have developed among government observers about government decentralization in Indonesia. Laws No. 22 and 25 of 1999 concerning Regional Government and Regional Finance, which were subsequently amended by Laws No. 22 and 33 of 2004, have led Indonesia to enter the process of decentralized governance after more than 30 years of being under the all-centralized New Order regime. The implementation of these two laws has become a momentum for the transfer of supervision, fiscal resources, political autonomy and responsibility for public services from the central government to local governments. Over the span of more than a decade of displacement, heterogeneous local experiences have surfaced, as central control over regions loosened. Local governments play a very important role in the implementation of decentralized fisheries management, apart from the central government, the community and other stakeholders with an interest in the fisheries sector, of course. They must be prepared to face challenges in managing the potential fisheries sector, so that there will be no more policies that harm the fishing community. So that the fishery sector is able to become the backbone of the country in eradicating poverty, injustice in government policies towards fishermen, and is able to become a contributor to foreign exchange for Indonesia.